2010
DOI: 10.1111/j.0105-2896.2010.00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Inherited defects in lymphocyte cytotoxic activity

Abstract: The granule-dependent cytotoxic activity of lymphocytes plays a critical role in the defense against virally infected cells and tumor cells. The importance of this cytotoxic pathway in immune regulation is evidenced by the severe and often fatal condition, known as hemophagocytic lymphohistiocytic syndrome (HLH) that occurs in mice and humans with genetically determined impaired lymphocyte cytotoxic function. HLH manifests as the occurrence of uncontrolled activation of T lymphocytes and macrophages infiltrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
131
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(135 citation statements)
references
References 110 publications
3
131
0
1
Order By: Relevance
“…3,49 In these models, hyperactive T cells are a key factor in disease pathogenesis. 2,50 It was, therefore, surprising that, paradoxically, a significant number of patients with T-cell deficiencies, including several patients without detectable circulating T cells, developed the HLH syndrome. Notably, at least three T-cell deficient X-SCID patients also had ≤10/μL NK cells, rendering it unlikely that hyperactivated NK cells replaced T cells as a pathogenic factor in these cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,49 In these models, hyperactive T cells are a key factor in disease pathogenesis. 2,50 It was, therefore, surprising that, paradoxically, a significant number of patients with T-cell deficiencies, including several patients without detectable circulating T cells, developed the HLH syndrome. Notably, at least three T-cell deficient X-SCID patients also had ≤10/μL NK cells, rendering it unlikely that hyperactivated NK cells replaced T cells as a pathogenic factor in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Xlinked lymphoproliferative syndromes (XLP1 and XLP2). 2 Impaired lymphocyte cytotoxicity with highly activated, but inefficient T cells are the main pathogenic factors in the former group of disorders, 3 while the pathophysiological basis of HLH in XLP and other syndromes of EBV susceptibility is less well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Haemophagocytic lymphohistiocytosis (HLH) is a potentially life-threatening condition characterized by abnormal activation and proliferation of polyclonal CD8 + T lymphocytes and macrophages that infiltrate multiple organs and overproduce inflammatory cytokines including c-interferon, interleukin (IL)6, and tumour necrosis factor-a (TNF-a) (Pachlopnik Schmid et al, 2010). HLH can be either primary, often associated with genetic mutations resulting in defective cytotoxicity (Gupta & Weitzman, 2010) or secondary to malignancies, autoimmune disorders, or infections (Rouphael et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenesis of HLH and MAS may be explained by uncontrolled activities of macrophages and dendritic cells as a result of these mutations (4,5). In one study, syntaxin was reported in all exon analyses and heterozygous mutation was reported in the genes encoding Munc13-4 proteins in 5 of 14 subjects who developed MAS due to SJIA.…”
Section: Introductionmentioning
confidence: 99%